Pengaruh Pengangguran Dan Kemiskinan Terhadap Kekerasan Di Indonesia - Arifudin Arifudin; Lasya Safara Nabilla; Rahma Khoerunnisa; Jessica Rahman; Dani Danii (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Unemployment is a group of people who enter the workplace but do not find work or are actively looking for work. Poverty is the state of an individual or group of individuals lacking the ability to meet basic needs to maintain and improve a stable way of life. Violence is the behavior of a person or group of people that causes other people loss, or causes other people physical pain or damage to something. This research aims to understand the impact of unemployment and poverty on violence in Indonesia. The study's findings show that poverty and poverty have a negative impact on violence in Indonesia. This type of research is quantitative research with a population in Indonesia. The method used in the analysis is the Normality Test and Multiple Linear Regression Test. From reports measured at the Central Statistics Agency for 2015-2021, the data used is secondary data. From the research produced or the results of data taken from the Central Statistics Agency, it is clear that there is a lot of unemployment, poverty and violence in Indonesia